STUDY OF THE COMPRESSIVE STRENGTH OF CORN LEAVE ASH CONCRETE DUE TO IMMERSION IN SALT SOLUTION (NaCl) - Rafly Afif Alfarizy Pane (Jurnal Teknik Sipil USU, 2021)
Concrete is a composite building material made from a combination of aggregate and cement paste which is very commonly used. Based on its geographical location, Indonesia is an archipelagic country with a fairly wide sea territory. Indonesia is an agricultural country, where agricultural land still dominates. One type of agriculture that is often found is corn. Therefore, a study was made to examine the extent to which the resistance of the concrete used is normal concrete and concrete built with the addition of corn leaf ash. The research method used is an experimental study in the laboratory. This is done 3 (three) variations of the addition of the initial ADJ proportion and NaCl soaking solution with a concentration of 0% (control); 3.5% and 10.5%. reached the age of 1 month, 2 months, 3 months, and 4 months. Based on research on the compressive strength of concrete with ADJ 0%; ADJ 15% and ADJ 10% experienced a decrease in compressive strength at the age of 1 month, 2 months, and 3 months At the age of 4 months the concrete experienced a decrease in compressive strength. The ADJ variation that gives the greatest compressive strength of concrete is in ADJ concrete with an ADJ percentage of 10 % in 3.5% NaCl and 10.5% NaCl baths, respectively 34.8